2022
DOI: 10.3390/healthcare10020319
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Practice of Forensic Medicine: An Overview

Abstract: During the COVID-19 pandemic, forensic sciences, on the one hand, contributed to gaining knowledge about different aspects of the pandemic, while on the other hand, forensic professionals were called on to quickly adapt their activities to respond adequately to the changes imposed by the pandemic. This review aims to clarify the state of the art in forensic medicine at the time of COVID-19, discussing the following: the influence of external factors on forensic activities, the impact of autopsy practice on COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 118 publications
(127 reference statements)
1
14
0
Order By: Relevance
“…During the autopsy, Letulle’s block was performed with subsequent organ fixation in formalin. Consistent with the studies of subjects who died from COVID-19 [ 28 , 34 ], on H&E staining, the lungs showed massive interstitial pneumonia, areas of inflammation with interstitial lympho-plasma cell infiltrate, and an interstitial edema. The liver showed granulocytes within the liver parenchyma.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…During the autopsy, Letulle’s block was performed with subsequent organ fixation in formalin. Consistent with the studies of subjects who died from COVID-19 [ 28 , 34 ], on H&E staining, the lungs showed massive interstitial pneumonia, areas of inflammation with interstitial lympho-plasma cell infiltrate, and an interstitial edema. The liver showed granulocytes within the liver parenchyma.…”
Section: Discussionsupporting
confidence: 85%
“…Autopsies conducted on subjects who died of COVID-19 showed pulmonary embolism, diffuse alveolar damage (DAD), hyaline membranes, thromboembolism, and interstitial edema with heterogeneous inflammatory tissue. Centrilobular necrosis and moderate portal or lobular inflammation are described in the liver [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…With multiple COVID-19 vaccines being introduced across the globe to a widely diverse population, people have become increasingly concerned about the risks associated with vaccines. Efforts to surveille, identify and report adverse events following immunization (AEFIs) are particularly important for preserving and restoring confidence in vaccination programs and combating vaccine hesitancy [106,107]. In this context, AEFI post-mortem investigations have been instrumental in establishing the causality relationship between vaccine administration and fatal adverse events, as well as identifying the cause of death in such cases [106][107][108].…”
Section: Sars-cov-2 Immunization In the Apac Regionmentioning
confidence: 99%
“…Efforts to surveille, identify and report adverse events following immunization (AEFIs) are particularly important for preserving and restoring confidence in vaccination programs and combating vaccine hesitancy [106,107]. In this context, AEFI post-mortem investigations have been instrumental in establishing the causality relationship between vaccine administration and fatal adverse events, as well as identifying the cause of death in such cases [106][107][108]. Concerns due to the persistence of high viral loads in exhumed corpses after a long post-mortem interval in spite of appropriate burial practices [109] highlight the importance of implementing shared guidelines for the safety of handling of COVID-19-positive and potentially infectious corpses during autopsy practices [106,109,110].…”
Section: Sars-cov-2 Immunization In the Apac Regionmentioning
confidence: 99%
“…Knowing the state of our immune system with traditional methods of measuring cellular and humoral immunity in a pandemic situation is complex [ 3 ], expensive, and invasive, so we need simple tools that give us an immediate response to our current needs and thus distribute the doses of vaccines to those who really need them [ 4 ]. In this brief report, we tried to assess with a simple, cheap, and easy-to-interpret test, a first step to study the immune response in vaccinated individuals 6 months after the start of the immunization scheme with 2 doses of an mRNA vaccine [ 5 ].…”
Section: Introductionmentioning
confidence: 99%